Pendampingan dalam Meningkatkan Kualitas Pendidikan Al-Qur’an dengan Metode An-Nahdliyah di TPQ Roudlotul Athfal Banjarwati Paciran Lamongan - Yanti, Siti Mahmudah; Rosikh, Fahrur (Universitas Sunan Drajat Lamongan, Indonesia, 2024)
Al-Qur’an is the main source of Islam religion and the third pillars of iman that must be belived by the moslems.Therefore, studying Al-Qur’an is a must for all moslems. In the process of learning Al-Qur’an, there will be many obstacles and many methods.One of the methods of learning Al-Qur’an is by using An-Nahdliyah method.it is kind of partysipatory Action Research in TPQ Roudhlotul Athfal, Banjarwati villige Paciran District,Lamongan Regency. The method of PAR approach is research method which invites the individuals and communities to be active participant by joining the activities, constructions or the same fasilities with their own knowladges. There are 4 steps done: 1. Observation, 2. Planning, 3. Implementation, and 4. Evaluation. This study shows that many student significantly get many improvements. It is known that the students are more active to join the class and able to differenciate the similar hijaiyah latters. The students also more accurarately know the long or short way of reading Al-Qur’an.